2015
DOI: 10.1016/j.pjnns.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Association of migraine headaches with anatomical variations of the Circle of Willis: Evidence from a meta-analysis

Abstract: Migraine is associated with anatomical variations in both the anterior and posterior portions of the COW. However, larger prospective trials are needed to determine the true prevalence of variations and their pathological significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
(23 reference statements)
0
13
0
1
Order By: Relevance
“…Several studies have reported an increased prevalence of CoW variants in people with migraine in comparison to the controls, in particular in migraineurs with aura and in the posterior circulation (Bugnicourt et al., ; Cavestro et al., ; Cucchiara et al., ; Henry et al., ). However, in most studies, the frequency of CoW variants in the control group was less than 50% which is considerably lower than expected from population based studies (El‐Barhoun, Gledhill, & Pitman, ; Kapoor, Singh, & Dewan, ; Krabbe‐Hartkamp et al., ; Li et al., ; Riggs & Rupp, ) and the 85% we found (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported an increased prevalence of CoW variants in people with migraine in comparison to the controls, in particular in migraineurs with aura and in the posterior circulation (Bugnicourt et al., ; Cavestro et al., ; Cucchiara et al., ; Henry et al., ). However, in most studies, the frequency of CoW variants in the control group was less than 50% which is considerably lower than expected from population based studies (El‐Barhoun, Gledhill, & Pitman, ; Kapoor, Singh, & Dewan, ; Krabbe‐Hartkamp et al., ; Li et al., ; Riggs & Rupp, ) and the 85% we found (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…CoW variants may be congenital but can also be acquired when patients get older (Zaninovich, Ramey, Walter, & Dumont, 2017). Some (Bugnicourt et al, 2009;Cavestro et al, 2011;Cucchiara et al, 2013;Henry et al, 2015), but not all (Schoonman, van Oosterhout, Ferrari, & van der Grond, 2010;Ezzatian-Ahar et al, 2014;Ikeda et al, 2017), studies report a higher frequency of incomplete CoW in migraine patients compared with controls in particular for the posterior circulation and in patients with migraine with aura.…”
Section: Introductionmentioning
confidence: 99%
“…Items for the AQUA Tool were generated on the basis of (1) the extensive background of the steering committee in conceiving and executing anatomical metaanalyses and systematic reviews, and (2) a review of the anatomical literature (Andall et al, 2015;Henry et al, 2015aHenry et al, , 2015bRamakrishnan et al, 2015;Roy et al, 2015;Tomaszewski et al, 2016aTomaszewski et al, , 2016bTomaszewski et al, , 2016cTomaszewski et al, , 2016dVikse et al, 2016). No comprehensive systematic review of systematic reviews was performed because there was no previously-used quality assessment of anatomical studies, and the number of true evidence-based reviews and meta-analyses in the literature is limited.…”
Section: Preliminary Conceptual Design and Item Generationmentioning
confidence: 99%
“…), and the extensive background of the steering committee in conducting meta-analyses and systematic reviews of anatomical studies (Andall et al, 2015;Henry et al, 2015aHenry et al, , 2015bRamakrishnan et al, 2015;Roy et al, 2015aRoy et al, , 2015bTomaszewski et al, 2016aTomaszewski et al, , 2016bTomaszewski et al, , 2016cTomaszewski et al, , 2016dVikse et al, 2016), we developed a preliminary conceptual design for the AQUA Checklist. In addition to items considered standard in reporting all medical studies (sample size, demographics, results, etc.…”
Section: Preliminary Conceptual Design and Item Generationmentioning
confidence: 99%
“…In that context, the authors of the present study have developed the Anatomical Quality Assurance (AQUA) Checklist, the aim of which is to improve the quality of reporting of anatomical studies. From our extensive experience of evidence-based anatomical studies (Andall et al, 2015;Henry et al, 2015aHenry et al, , 2015bRamakrishnan et al, 2015;Roy et al, 2015aRoy et al, , 2015bTomaszewski et al, 2016aTomaszewski et al, , 2016bTomaszewski et al, , 2016cTomaszewski et al, , 2016dVikse et al, 2016), we have found that such studies are often poorly reported, thus decreasing their reliability and increasing the risk of bias. A high reporting quality is imperative since understanding and knowledge of anatomy allows for successful clinical interventions.…”
Section: Introductionmentioning
confidence: 99%